2008
DOI: 10.1242/jeb.011791
|View full text |Cite
|
Sign up to set email alerts
|

Active control of free flight manoeuvres in a hawkmoth, Agrius convolvuli

Abstract: SUMMARYBy combining optical triangulation with the comb-fringe technique and dual-channel telemetry, wing kinematics and body attitudes accompanying muscle activities of free-flying male hawkmoths were recorded synchronously when they performed flight manoeuvres elicited by a female sex pheromone. The results indicate that the wing leading edge angular position at the ventral stroke reversal, which can be decomposed by two orthogonal angular parameters (a flapping angle and a deviation angle), is well controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
6
60
0
Order By: Relevance
“…In particular, the DVMs, located near the wing hinges, would effectively deform the lateral scutum and control the wings. Recent studies have reported the contribution of the powerproducing IFMs to lateral control in both the synchronous [4][5][6] and the asynchronous types [10]. The multiple functions of the IFMs provide flexibility for flight control and will be further elucidated by a combination of morphometry, physiology and computational structural analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the DVMs, located near the wing hinges, would effectively deform the lateral scutum and control the wings. Recent studies have reported the contribution of the powerproducing IFMs to lateral control in both the synchronous [4][5][6] and the asynchronous types [10]. The multiple functions of the IFMs provide flexibility for flight control and will be further elucidated by a combination of morphometry, physiology and computational structural analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Lepidoptera can use the neurogenic controllability of the IFMs for finer control of wing kinematics, while at the same time gaining mechanical benefits. Previous studies of hawkmoths have shown that phase asymmetry in the activity of bilateral IFMs can generate asymmetry in the power and kinematics of the wing beat [4][5][6]. To achieve such asymmetrical control, the single structure of the mesonotum can be locally deformed and transmit asymmetrical power to the wings.…”
Section: Introductionmentioning
confidence: 99%
“…We correlate dorsal longitudinal muscle (DLM; wing depressor muscle) and dorsal ventral muscle (DVM; wing elevator muscle) bilateral activation phase differences with yaw velocity and yaw acceleration. Though the DLM and DVM have historically been categorized as 'power' muscles (Pringle, 1957), there is growing evidence (Sponberg and Daniel, 2010;Tu and Daniel, 2004;Wang et al, 2008) that flying insects with synchronous flight muscles (e.g. moths) may, like vertebrate flyers (Hedrick and Biewener, 2007b), modulate main flight muscle power output during manoeuvres.…”
Section: Introductionmentioning
confidence: 99%
“…This can either be avoided by using implantable electrodes and then having the animal move on a long tether (i.e. Clarac et al, 1987;Duch & Pflüger, 1995;Böhm et al, 1997;Gruhn & Rathmayer, 2002) or by transmitting the data using telemetric devices (Kutsch et al, 1993;Fischer et al, 1996;Tsuchida et al 2004;Hama et al, 2007;Wang et al, 2008). Both of these elegant methods, which are successfully used in larger arthropods, often prove difficult to apply in smaller walking insects which either easily get entangled in the long tether or are hindered by the weight of the telemetric device and its batteries.…”
Section: Introductionmentioning
confidence: 99%